STRATEGI PENDIDIKAN AGAMA ISLAM BAGI PASANGAN PERNIKAHAN DINI DALAM MEMBENTUK KELUARGA SAKINAH - Dia Ayuni Lestari; Abdul Jalil; Ach. Faisol (VICRATINA, 2019)
Every religion has different ways and rules in regulating relations between men and women, one of which is a marriage bond (Abd. Kadir. 2001). Marriage is a necessity in Islam for those who have been considered capable, therefore anyone must fulfill the procedures that apply in religion and local culture. Marriage is the instinct of life for humans not only oriented to sex drive but also to the prevailing norms. This article aims to find out the strategy of Islamic education applied by couples of early marriages to create a sakinah family. The method used in this study is the method of observation, interviews and documentation approach using a qualitative approach. The strategies carried out by adult couples are mostly more systematic and planned because the ability of good thinking patterns and maturity between men and women certainly becomes a big question how do couples marry early in applying the Islamic religious strategy in fostering a family to a peaceful family.